Lee Kuan Yew’s China wisdom - Hoo, Tiang Boon (2015)
As the rare statesman who has engaged all five generations of Chinese leadership, Lee Kuan Yew had a deep and profound understanding of China. Policymakers and scholars would do no worse than to overlook Lee’s insights on the rising power.